Controlling structure of vertically grown graphene sheets on carbon fibers for hosting Li and Na metals as rechargeable battery anodes. (March 2020) - Ji, Xixi; Lin, Zijia; Zeng, Jie; Lin, Yanhong; Mu, Yongbiao; Wang, Shuguang; Ren, Zhonghua; Yu, Jie
Abstract: Metallic Li/Na anodes are highly attractive for next-generation batteries due to their high capacity and low anode potential. But dendrite growth and huge volume change during long-term cycling hinder their practical application. Here, vertical graphene sheets grown on carbon fibers (VGSs/CFs) prepared by thermal chemical vapor deposition are used as 3D stable hosts for Li/Na metal anode. The results show that the structure of the VGSs has great influence on electrochemical performance of the anodes. The tightly interconnected VGSs provide numerous active sites for Li/Na adsorption and improve electrical conductivity of the anodes, increasing current density uniformity and decreasing energy barrier for the Li/Na nucleation on the composite electrode during cycling. The symmetrical cell based on VGSs/CFs composite Li anode (Li/VGSs/CFs) demonstrates a small overpotential of 76 mV for 1200 cycles at 5 mA cm −2 in carbonate-based electrolyte. The symmetrical cell using VGSs/CFs composite Na anode (Na/VGSs/CFs) shows a small overpotential of 98 mV for 2000 cycles at 10 mA cm −2 . Furthermore, in full-cell configurations against Li4 Ti5 O12 or LiFePO4 cathodes, Li/VGSs/CFs anode displays ultrahigh cyclic stability and rate performance. The Li/VGSs/CFs and Na/VGSs/CFs anodes outperform the reported hosts for Li/Na anodes and are of high promise for practical application. Graphical abstract: Image 1